Communication in microgrids and virtual power plants - Starynets, Oleksandr (UiT Norges arktiske universitet, 2016)
One of the cornerstones of the steady operation of microgrids and virtual power plants as building blocks for smart grid is the communication system, which is the main objective for evaluation and research in this thesis. The given project investigates the most widespread communication protocols along with IEC 61850 standard for substations automation applied in smart grids. Based on the presented analysis for communication technologies and protocols the appropriate communication solution for the laboratory microgrid at UiT – The Arctic University of Norway (Campus Narvik) is suggested and implemented